Problemy etyczne negocjacji w biznesie - Kałążna-Drewińska, Urszula (Ethical Problems of Business Negotiations, 2007)
The framework of the paper's content is as follows: 1. Comprehension and essence of ethics in negotiations. 2. Objectives and areas of ethics in negotiations. 3. Causes of unethical behaviour as well as criteria of proper behaviour appraisal.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 106-112